Flow cytometry-based isolation of tumor-associated regulatory T cells and assessment of their suppressive potential - Kos, Kevin; van Baalen, Martijn; Meijer, Denize A; de Visser, Karin E (Methods in enzymology, 2020)
Regulatory T cells (Tregs) play a major role in establishing an immunosuppressive tumor microenvironment. In order to fully uncover their role and molecular regulation in tumor-bearing hosts, it is critical to combine phenotypical characterization with functional analyses. A standard method to determine the suppressive potential of Tregs is with an in vitro suppression assay, in which the impact of freshly isolated Tregs on T cell proliferation is assessed. The assay requires the isolation of substantial numbers of Tregs from tissues and tumors, which can be challenging due to low yield or cell damage during sample preparation. In this chapter, we discuss a flexible suppression assay which can be used to assess the suppressive potential of low numbers of murine Tregs, directly isolated from tumors. We describe methods for tissue preparation, flow cytometry-based sorting of Tregs and optimal conditions to perform a suppression assay, to obtain reliable and reproducible results.